Food security and import substitution In the Russian Federation in the post-soviet period - Yashkova Tatyana (EDP Sciences, 2021)
The article is devoted to the problem of ensuring the food security of the Russian Federation and the issue of import substitution in the context of increasing geopolitical confrontation, the adoption of sanctions and retaliatory measures, and the deterioration of the economic situation due to the pandemic. The article examines the dynamics of the processes of ensuring the country's food security in the last three decades. The expediency of using the import substitution policy as a tool for ensuring food security is justified. Recommendations are formulated to optimize the processes of import substitution and increase the level of food security. The authors propose comprehensive measures based on current global trends in macroeconomic development and the state of food security in the Russian Federation. Special attention is paid to the expediency of carrying out large-scale work on scientific justification, strategic goal setting and planning, the development of multi-variant scenarios for the development of the situation in the field of food security under the influence of changing factors, with the involvement of a large number of experts and the use of advanced approaches and modern methods.